Differences in mobility and dispersal capacity determine body size clines in two common alpine-tundra arthropods - Beckers, Niklas; Hein, Nils; Anneser, Alessa; Vanselow, Kim; Löffler, Jörg (Insects, 2020)
The Arctic is projected to be severely impacted by changes in temperature and precipitation. Species react to these changes by shifts in ranges, phenology, and body size. In ectotherms, the patterns of body size clines and their underlying mechanisms are often hard to untangle. Mountains provide a space-for-time substitute to study these shifts along multiple spatial gradients. As such, mobility and dispersal capacity might conceal reactions with elevation. We test this influence on body size clines by comparing two common arthropods of the alpine tundra. We find that high mobility in the lycosid spider Pardosa palustris blurs elevational effects. Partially low mobility at least during development makes the carabid beetle Amara alpina more susceptible to elevational effects. Specific life-history mechanisms, such as brood care in lycosid spiders and holometabolic development in carabid beetles, are the possible cause.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Bergmann’s rule; Elevational gradients; Genus: Amara; Genus: Pardosa; Life-history; Size rule; Species: Amara alpina; Species: Pardosa palustris; Temperature